Survey and Biological Activity of Economic Plants of Kheri Forests, Uttar Pradesh - Singh, K. K.; Bhati, H. S.; Maheshwari, J. K. (Indian Forester, 1979)
The forest areas of Kheri district adjoining Indo-Nelpal Border have been explored from the point of view of the availability of economie and medicinal plants used either in indigenous system of medicine or by the local people. The present communication gives information On therapeutic properties of 89 species belonging to 44 families of plants inbabiting the forest areal of the district. The Vegetable resources of the district are quite rich in raw materials for the local cottage industries like Kattha, paper mill, timber and minor forest products.